Management of Paediatric Patients With Medically Refractory Crohn's Disease Using Ustekinumab: A Multi-Centred Cohort Study. (12th December 2018) - Chavannes, Mallory; Martinez-Vinson, Christine; Hart, Lara; Kaniki, Nicole; Chao, Che-Yung; Lawrence, Sally; Jacobson, Kevan; Hugot, Jean-Pierre; Viala, Jérome; Deslandres, Colette; Jantchou, Prevost; Seidman, Ernest G
Abstract: Background: Ustekinumab [UST] is effective in the treatment of adults with moderate to severe Crohn's disease [CD]. There is a paucity of data on its use in children. Aim: To evaluate the response to UST in children with moderate to severe CD. Methods: This multicentre retrospective cohort study identified children under 18 years old with CD, who received open-labelled subcutaneous UST. The primary outcome was changes in mean abbreviated Paediatric Crohn's Disease Activity Index [aPCDAI] between baseline and 3 and 12 months, and rate of clinical remission at 3 and 12 months. Secondary outcomes were clinical response at the same time points, changes in C-reactive protein [CRP] and albumin, improvement in growth parameters, and rate of adverse events. Results: A total of 44 patients who failed at least one biological treatment were identified. Linear mixed model [LMM] analysis revealed a statistically significant effect of UST (χ2[1] = 42.7, p = 1.2 × 10 –8 ) which lowered the aPCDAI scores by about 16 ± 2.7 at 3 months, and 19.6 ± 2.9 at 12 months. At 12 months, 38.6% of the patients achieved clinical remission and 47.8% achieved clinical response. There was a significant increase in mean weight z-score of 0.48 [±0.13] [ p <0.001] and in mean body mass index [BMI] z score of 0.66 [±0.16] [ p <0.001]. The probability of remaining on UST at 12 months was 76.9%. The rate of adverse events was 12.4 per 1000 patient-months. Conclusions: Subcutaneous UST should be considered a viable therapeutic option for paediatric patients who are refractory to other biological agents. Prospective randomised trials are needed.